Enzymatic processes of the organic matter transformation and regeneration of nutrients in the ecosystem of the White Sea. - Agatova, Alina I; Lapina, N M (PANGAEA, 2004)
Rates of organic matter (OM) transformation within the production-destruction cycle of the White Sea were estimated on the basis of measured activity values of redox enzymes of the electron transport system and of hydrolytic enzymes (phosphatase and protease). It was found that OM oxidation processes were the most intensive in the Kandalaksha Bay, while minimum oxidation rates were characteristic of central parts of the Dvina and Onega bays. It was revealed that the highest rates of phosphate mineralization were characteristic of the central part of the sea and near-mouth areas of the Onega and Kandalaksha bays, with the lowest rates in the Dvina Bay. During the period of intense primary production when resources of inorganic phosphorus were practically depleted, high rates of phosphate regeneration were observed. It was shown that populations of micro- and zooplankton in the White Sea were characterized by low activation energies of the principal metabolism reactions (3-6 kcal/mol), which allowed these populations to provide exchange intensity comparable to that of inhabitants of warm waters during all the seasons.
Rates of organic matter transformation within the production-destruction cycle of the White Sea
Keywords: AL-2004-1; AL-2004-2; AL-2004-3; Archive of Ocean Data; ARCOD; Bottle, Niskin; NIS; White Sea